The role of zakat in Islamic macroeconomics: A fiscal instrument for stability during global economic crises‎ - Mustamin, Siti Walida; Abdillah S., Abdillah S.; Mansyur, Fakhruddin; Ridwan, Muhammad; Amri, Ulil; Fitrayani, Fitrayani (Universitas Islam Indonesia, 2025)
IntroductionThe global economic crisis continues to expose weaknesses in conventional fiscal systems, prompting the search for alternative macroeconomic instruments. Within Islamic economic thought, zakat—traditionally viewed as a religious obligation—emerges as a redistributive tool capable of addressing structural inequality, stabilizing consumption, and supporting vulnerable populations during periods of financial instability.ObjectivesThis study explores the macroeconomic contribution of zakat in times of global economic crisis. It specifically investigates zakat’s potential as a countercyclical fiscal instrument that enhances aggregate demand, reduces poverty, and alleviates fiscal pressure on national governments.MethodUsing a qualitative literature review methodology, this research synthesizes scholarly articles, institutional reports, and classical Islamic economic texts published between 2000 and 2024. The analysis follows a thematic approach, focusing on zakat’s functions in promoting wealth redistribution, economic resilience, and long-term fiscal sustainability.ResultsFindings reveal that zakat plays a critical role in mitigating economic shocks. It stimulates liquidity by enhancing consumption among low-income groups, supports grassroots economic development through community-based aid, and reduces government spending by acting as a complementary social safety net. Empirical evidence from Muslim-majority countries indicates that institutionalized zakat systems are effective in reducing poverty and inequality, particularly during economic downturns.ImplicationsIntegrating zakat into national fiscal policy frameworks could provide a sustainable, ethical, and community-driven response to financial crises. Effective governance, transparency, and technological innovation in zakat administration are essential to maximize its economic impact and maintain public trust.Originality/NoveltyThis study repositions zakat from a purely religious practice to a strategic economic instrument within Islamic macroeconomics. It offers a normative and conceptual foundation for embedding zakat in contemporary fiscal systems as a means of achieving economic stability, social equity, and inclusive recovery in times of crisis.